2020
DOI: 10.1007/s00127-020-01990-x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of clinical staff working in high-risk epidemic and pandemic health emergencies a rapid review of the evidence and living meta-analysis

Abstract: Purpose The SARS-CoV-2 / COVID-19 pandemic has raised concerns about the potential mental health impact on frontline clinical staff. However, given that poor mental health is common in acute medical staff, we aimed to estimate the additional burden of work involving high exposure to infected patients. Methods We report a rapid review, meta-analysis, and living meta-analysis of studies using validated measures from outbreaks of COVID-19, Ebola, H1N1 influenza, Middle East respiratory syndrome (MERS), and sever… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 96 publications
4
52
0
4
Order By: Relevance
“…While the sample size was limited, a total of 47.1% of the respondents reported having high levels of social isolation (score above 6.0 units on a scale of 0–12). These findings were consistent with reports from Rosenberg and colleagues (2020) that the prevalence of loneliness was 54% during the COVID-19 pandemic in April 2020 [ 14 ]. Our study was conducted in March 2021 when restrictions were relatively relaxed, resulting in slightly lower rates of social isolation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While the sample size was limited, a total of 47.1% of the respondents reported having high levels of social isolation (score above 6.0 units on a scale of 0–12). These findings were consistent with reports from Rosenberg and colleagues (2020) that the prevalence of loneliness was 54% during the COVID-19 pandemic in April 2020 [ 14 ]. Our study was conducted in March 2021 when restrictions were relatively relaxed, resulting in slightly lower rates of social isolation.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have suggested that COVID-19 preventive behaviors may result in greater odds of reporting loneliness and social isolation [ 11 , 12 , 13 ]. For instance, a population-based study in the United States (U.S.) examining the impact of COVID-19 social distancing and preventive behaviors found that 54% of participants reported loneliness [ 14 ]. Loneliness was associated with more significant depressive symptoms among people with fewer social interactions than those who had more frequent in-person social interactions or connections [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic has created a range of extraordinary strains on healthcare workers: as well as exposure to a potentially deadly infection that could affect them directly or be transmitted to their families, staff may be routinely faced with traumatising situations, the deaths of patients they have cared for the need to take highly consequential decisions under severe pressure. (7) The need to attend to the mental health of healthcare workers was raised early in the pandemic. (8,9) Much of the focus of attention and research on the impacts of the pandemic to date has been on those working in acute medical settings, including, for example, intensive care units.…”
Section: Introductionmentioning
confidence: 99%
“…(8,9) Much of the focus of attention and research on the impacts of the pandemic to date has been on those working in acute medical settings, including, for example, intensive care units. (7) (10) The di culties confronted by those working in mental healthcare settings, both in-patient and in the community, have been less well scrutinised and understood, but are no less important; working practices have changed dramatically (11)(12)(13) while population need and referrals to care are likely to continue to increase. In this article, we respond to this void in the literature, reporting an interview-based qualitative study that seeks to characterise the challenges faced by those working in NHS mental health settings during the rst wave of the Covid-19 pandemic in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Although context sensitivity was inversely associated with positive affect at higher levels of perceived financial strain, in general, context sensitivity and responsiveness to feedback were linked with lower anxiety and depressive symptoms. Cultivating regular daily routines in everyday life may be a simple and effective intervention in reducing psychological distress [ 78 , 79 , 80 , 81 ], especially for persons with less socioeconomic resources (e.g., low savings, no home ownership) in times with multiple large-scale stressors such as civil unrest and pandemic [ 82 ].…”
Section: Discussionmentioning
confidence: 99%